2020
DOI: 10.1063/1.5141818
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between uniaxial magnetic anisotropic constant and in-plane tensile strain in Mn4N epitaxial films

Abstract: Ferrimagnetic Mn4N is a promising candidate for current-induced domain wall motion assisted by spin-transfer and spin–orbit torques. Mn4N can be doped to have perpendicular magnetic anisotropy (PMA) and a small spontaneous magnetization. However, the origin of the PMA of Mn4N has yet to be fully understood. Here, we investigated the relationship between the ratios of the perpendicular lattice constant c to the in-plane lattice constant a of Mn4N epitaxial thin films (c/a) and the uniaxial magnetic anisotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…The Mn-atoms at the corner and the face center have inequivalent magnetic moments and are ferrimagnetically coupled 21 . Although the easy axis of bulk Mn4N is along the [111] direction, PMA is repeatedly and reproducibly observed in crystalline Mn4N films [22][23][24][25][26][27][28] . As a result, ferrimagnetic Mn4N thin films have also attracted increasing interest in spintronics applications.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The Mn-atoms at the corner and the face center have inequivalent magnetic moments and are ferrimagnetically coupled 21 . Although the easy axis of bulk Mn4N is along the [111] direction, PMA is repeatedly and reproducibly observed in crystalline Mn4N films [22][23][24][25][26][27][28] . As a result, ferrimagnetic Mn4N thin films have also attracted increasing interest in spintronics applications.…”
mentioning
confidence: 87%
“…As noted earlier, the emergence of PMA is an important magnetic property for its use in spintronic applications. One of the plausible reasons for the PMA in Mn4N thin films could be attributed to the deviation of the out-of-plane lattice constant, c, to the in-plane lattice constant, a, (c/a) ratio from 1, [22][23][24][25][26][27][28] due to the in-plane epitaxial strain. A recent study also showed that the anisotropy energy is correlated to the c/a ratio 27 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One promising candidate with superior thermal stability compared to the amorphous rare-earth transition metals is rare-earth-free Mn 4 N. There are some key similarities and differences between the rare-earth transition metals and Mn 4 N. Both are ferrimagnetic metals, and there have been successful experimental demonstrations of thin film growth in both systems. Both materials show perpendicular magnetic anisotropy (PMA) in the thin film geometry 16,[20][21][22][23][24][25][26][27] . However, unlike the amorphous structure in the rare-earth transition metals, Mn 4 N is a crystalline compound that forms in the anti-perovskite crystal structure 27 .…”
mentioning
confidence: 99%